SelfieArt: Interactive Multi-Style Transfer for Selfies and Videos with Soft Transitions - Alegre, Lucas Nunes; Oliveira, Manuel Menezes (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
We introduce SelfieArt, an interactive technique for performing multi-style transfer for portraits and videos. Our method provides a simple and intuitive way of producing exquisite artistic results that combine multiple styles in a harmonious fashion. It uses face parsing and a multi-style transfer model to apply different styles to the various semantic segments. This is achieved using parameterized soft masks, allowing users to adjust the smoothness of the transitions between stylized regions in real-time. We demonstrate the effectiveness of our solution on a large set of images and videos. Given its flexibility, speed, and quality of results, our solution can be a valuable tool for creative exploration, allowing anyone to transform photographs and drawings in world-class artistic results.